Using mid-upper arm circumference z-score measurement to support youth malnutrition screening as part of a global sports and wellness program and improve access to nutrition care - Sharn, Amy R.; Sorgho, Raissa; Sulo, Suela; Molina-Molina, Emilio; Rojas Montenegro, Clara; Villa-Real Guno, Mary Jean; Abdel-Rahman, Susan (Frontiers in Nutrition, 2024)
Objective: Historically, mid-upper arm circumference (MUAC) has been instrumental to identifying malnutrition in children under 5 years living in resource restricted settings. Less attention is directed to at-risk, school-aged youth. Updated and validated pediatric age- and gender-specific MUAC growth curves expand malnutrition screening opportunities (2 months-18 years) including overweight/obesity. An innovative partnership was created to integrate MUAC z-score measurement trainings and screenings in Real Madrid Foundation’s (RMF) Social Sports Schools (S3) program, which provide sports and wellness programming to under-resourced communities. This work investigated the feasibility of leveraging non-healthcare professionals (non-HCPs) to identify malnutrition risk as part of RMF S3. Methods: This global, two-part program on malnutrition risk identification included training adult facilitators and screening children attending RMF S3. RMF facilitators were trained with didactic lectures on malnutrition, and practical hands-on learning of proper MUAC z-score tape measurement. Aggregate data on facilitators and number of times to correctly administer the MUAC z-tape were recorded. Aggregate data on child malnutrition risk screenings were collected. Results: Nine countries participated representing Europe, Pacific Asia, Africa, Latin America, and North America. In total, 143 RMF facilitators were trained, and 318 children were screened across 11 sites. Majority of facilitators were male (56%, n=80), and majority were coaches (41.3%, n=59), followed by staff (25.2%, n=36), and volunteers (16.1%, n=23). Facilitator attempts ranged from 1 to 4 times for proper MUAC z-score administration with mean 2.12 (± 0.86). There were no significant differences for attempts among RMF facilitator types (p=0.10). Sixteen percent (n=51) of children screened were recommended for HCP referral, with concentrations in Pacific Asia (68%, n=35), Latin America (24%, n=12), and Africa (8%, n=4). Conclusions: Findings from our sample demonstrate that integration of MUAC z-score based malnutrition risk screening within community sports and wellness programming among non-HCPs is feasible, and that some regions with less frequent access to routine health care may experience greater benefit from these programs. Equipping non-HCP facilitators in community sports and wellness programs with malnutrition screening training provides a means to meet under-resourced families where they live to begin conversations around malnutrition risk with hope to establish pathways to care.